2008
DOI: 10.1080/01443610802149863
|View full text |Cite
|
Sign up to set email alerts
|

The incidence of uterine leiomyoma and other pelvic ultrasonographic findings in 2,034 consecutive women in a north London hospital

Abstract: New generation technologies provide alternative ways of assessing the female pelvis, and provide improved estimates of the incidence of uterine leiomyoma. To determine the incidence of uterine leiomyoma and other incidental findings, the request forms for pelvic ultrasound scan and the scan results of 2,034 consecutive women was reviewed. There were 586 women with scan-detected uterine leiomyoma giving an incidence of 29.9%, although only 3% of the women had clinically suspected leiomyoma. Pain was the leading… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 10 publications
2
16
0
Order By: Relevance
“…Development of myomas increases drastically throughout the subsequent decades of age, reaching 60% within the range between 40 and 60 years [11, 12]. Relation between obesity and augmented risk of myoma has now been well documented.…”
Section: Introductionmentioning
confidence: 99%
“…Development of myomas increases drastically throughout the subsequent decades of age, reaching 60% within the range between 40 and 60 years [11, 12]. Relation between obesity and augmented risk of myoma has now been well documented.…”
Section: Introductionmentioning
confidence: 99%
“…Uterine leiomyomata are highly prevalent, fibrotic tumors of the uterus that disproportionally afflict African American women and are a public health concern (Day Baird et al, 2003; Walker and Stewart, 2005; Lee et al, 2007; Selo-Ojeme et al, 2008; Laughlin et al, 2009). Previously, we (Catherino et al, 2004; Leppert et al, 2004), and others (Wolanska et al, 1998; Mitropoulou et al, 2001; Wolanska et al, 2003; Behera et al, 2007) have shown the ECM of leiomyoma to be increased in amount and altered in composition, compared to the ECM of the uterine myometrium.…”
Section: Introductionmentioning
confidence: 99%
“…: fibroids) are among the most frequent clinically relevant human tumors leading, e.g., to abdominal pain, bleeding and infertility. Their prevalence clearly differs depending on ethnicity but in most countries exceeds 50% of all women in their reproductive ages 1, 2. The monoclonal origin of fibroids3–6 suggests mutations of myometrial target cells as the cause of the disease.…”
mentioning
confidence: 99%